A construção do debate político e as condições para a cidadania do morador de periferia no programa televisivo Aglomerado - Lorena Rúbia Pereira Caminhas (2015)
The proposal of this research is to investigate how the TV show Aglomerado sets the political debate about the conditions necessary to ensure the citizenship of slum dwellers. There are three central questions that the study aims to answer: How the program organizes the media and political aspects of the interactions and the discourses involving the debate about citizenship? What are the conditions identified by the program as fundamental to enable the individuals to be citizens? To what extent the program configuration allows or shies away the production of the discussion about citizenship? To carry out the research two different axes will be developed: the first will discuss the importance of the media (and in particular television) for everyday life and for the political action of the subject, coupled with an analysis of the media organization of the program, which consists of observation of mediation is that its production and the examination of interactional devices (proximity and familiarity) and speaks places (living and belonging). The second will investigate the construction of a notion of citizenship within the program that directs the political debate, which will be extracted the necessary conditions for the slum dwellers are considered citizens - respect and recognition, the symbolic ghetto output and freedom of expression of themselves and their reality. The selected methodology is the case study, which directs the operation of the object both from a practical point of view - the steps taken to answer the question - as epistemological, directing the construction of the object of analysis. The corpus consists of four episodes of Aglomerado, among which two are first season and two are of second season, selected from the participants and the discussed issues: there are two episodes with the slum dweller (funk singers) and two with people who do not live in the suburbs (Lenin and Fernanda Abreu); the themes are the culture developed in the periphery and forms of discrimination suffered by its residents. Through this research was realized that Aglomerado is built through a fundamental tension between the objectives presented and choices made in the media and political spheres, which reverberate in an ambiguity in the formulation of the essential conditions for citizenship of the slum dwellers.